Application of whole blood and peripheral blood progenitor cells (PBPC) and new strategies for rescue after intensive cyclic chemotherapy in high-risk breast cancer - Filip, S; Bláha, M; Odrázka, K; Mericka, P; Vávrová, J (Journal of hematotherapy & stem cell research, 2000)
The efficacy of autologous peripheral stem cells given as mobilized whole blood or leukapheresis product for hematopoietic rescue after intensive chemotherapy was studied in 34 consecutive female patients with high-risk breast cancer. All patients received six cycles of chemotherapy regimen EC (epirubicin 150 mg/m2 and cyclophosphamide 1250 mg/m2) at 14-day intervals. In the first cycle, chemotherapy was given on day 1, and 24 h later mobilization of PBPC was started with G-CSF at a dose of 5 microg/kg/day for 13 days. In all other cycles, G-CSF was given at the same dose from day 7. On days 11, 12, and 13, leukaphereses were performed, and whole blood was collected on day 14 (the peak incidence of colony-forming units-granulocyte-macrophage [CFU-GM] burst-forming units-erythrocyte [BFU-E], and colony-forming unit-granulocyte-erythrocyte-macrophage-megakaryocyte [CFU-GEMM]). The second cycle of chemotherapy was started on day 15, and 24 h later, whole blood (collected in the first cycle) was reinfused, and the same was done in the third cycle. In the fourth to sixth chemotherapy cycles, leukapheresis product was used for hematopoietic rescue. The median increment of absolute values in both whole blood and leukapheresis product was as follows: CD34+ cells over baseline was approximately 17.4-fold, CFU-GM was 85.3-fold, BFU-E was 95.9-fold, and CFU-GEMM was 44.2-fold. In the cycles with whole blood support, the mean values of applied progenitors per cycle were CD34+ cells 1.52 x 10(6)/kg, CFU-GM, 1.18 x 10(5)/kg, BFU-E 2.54 x 10(5)/kg, CFU-GEMM 0.31 x 10(5)/kg. In the courses with PBPC support, the mean values of progenitors were CD34+ 2.04 x 10(6)/kg, CFU-GM 1.59 x 10(5)/kg, BFU-E 2.87 x 10(5)/kg, and CFU-GEMM 0.34 x 10(5)/kg. Leukopenia in patients supported with whole blood versus leukapheresed PBPC was as follows: grade 4, 13/6 (38.2%/17.6%), grade 3, 19/23 (55.9%/70.6%), and grade 2, 1/4 (2.9%/11.8%), respectively. Thrombocytopenia was grade 4, 11/6 (32.4%/17.6%), grade 3, 10/7 (29.4%/20.6%), grade 2, 7/13 (20.6%/38.2%), and grade 1, 6/6 (17.6%/17.6%), respectively. The median follow-up analysis was at 24.6 (7-36) months. High-risk patients previously treated with surgery and adjuvant chemotherapy (n = 5) were not evaluated for response. In 21 patients with locally advanced or inflammatory breast carcinoma the response rate (RR) was 94%, CR was 90%, and PR was 15%. No response to therapy was observed in 1 patient. In 8 patients with metastatic disease, RR was 75%, there was no CR, and PR was 75%. Two patients died during therapy. Relapse-free survival (RFS) in the adjuvant group was 23.7 (range 12-36) months and in the group with locally advanced disease was 18.2 (range 7-27) months. In the group with metastatic disease, time to tumor progression (TTP) was 12.1 (range 1-16) months. Mean duration of hospital stay for whole blood reinfusion in the second and third chemotherapy cycles was 6.7 (range 5-8) days and for PBPC in the fourth to sixth cycles was 6.2 (range 4-8) days, which at p < 0.001 was not statistically significant.
Keywords: dospělí; záchranná terapie; nádory prsu; Cyclophosphamide; Female; transfuze trombocytů; Stem Cells; Blood Transfusion; Adult; krevní transfuze; ženské pohlaví; výsledek terapie; Antigens, CD34; přežití bez známek nemoci; antigeny CD34; lidé; Hematopoietic Stem Cell Transplantation; autologní transplantace; transplantace hematopoetických kmenových buněk; leukopenie; mobilizace hematopoetických kmenových buněk; kmenové buňky; Breast Neoplasms; Platelet Transfusion; Salvage Therapy; Epirubicin; Hematopoietic Stem Cell Mobilization; následné studie; Treatment Outcome; Antineoplastic Combined Chemotherapy Protocols; Leukopenia; hospitalizace; protokoly protinádorové kombinované chemoterapie; faktor stimulující kolonie granulocytů; Middle Aged; Granulocyte Colony-Stimulating Factor; Follow-Up Studies; trombocytopenie; Hospitalization; Disease-Free Survival; epirubicin; Leukapheresis; lidé středního věku; Transplantation, Autologous; leukaferéza; Thrombocytopenia; cyklofosfamid; Humans